2011
DOI: 10.11606/s1413-95962011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-17β altera expressão proteica endometrial em fêmeas bovinas tratadas no 17º dia do ciclo estral

Abstract: ResumoEm fêmeas bovinas, a liberação de prostaglandina F 2a (PGF 2a ) é induzida in vivo pelo estradiol (E 2 ). Acredita-se que o E 2 estimule a síntese de proteínas essenciais na produção de PGF 2a . Objetivou-se avaliar o efeito do E 2 no incremento da concentração de proteínas totais e na modificação da composição proteica em explantes endometriais de fêmeas bovinas tratadas com E 2 no 17º dia do ciclo estral. Novilhas cruzadas foram tratadas no 17° dia do ciclo estral, via intravenosa, com 0 mg (Grupo Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In Oliveira (2017), the hypothesis that 17β-E 2 would stimulate was also rejected, which corroborates with our results (in Experiments 1 and 2). Alves et al (2011) demonstrated that in vivo treatment with 17β-E 2 did not modulate the total protein amount in endometrial explants collected 2 h after slaughter. There was also no modulation in the abundance of proteins with molecular weights similar to PKC (approximately 80 kDa).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In Oliveira (2017), the hypothesis that 17β-E 2 would stimulate was also rejected, which corroborates with our results (in Experiments 1 and 2). Alves et al (2011) demonstrated that in vivo treatment with 17β-E 2 did not modulate the total protein amount in endometrial explants collected 2 h after slaughter. There was also no modulation in the abundance of proteins with molecular weights similar to PKC (approximately 80 kDa).…”
Section: Discussionmentioning
confidence: 92%
“…There was also no modulation in the abundance of proteins with molecular weights similar to PKC (approximately 80 kDa). However, Alves et al (2011) reported an increase in the number of proteins with molecular weights of 75 to 76 kDa and 108 to 110 kDa. Thus, it is suggested that other proteins, which we did not evaluate, may modulate PGF2α synthesis by stimulating 17β-E 2 .…”
Section: Discussionmentioning
confidence: 99%